Impact of the timeliness of antibiotic therapy on the outcome of patients with sepsis and septic shock. Issue 5 (May 2021) - Asner, Sandra A.; Desgranges, Florian; Schrijver, Irene T.; Calandra, Thierry
Summary: Objectives: To review the impact of the timeliness of antibiotic therapy on the outcome of patients with sepsis or septic shock. Methods: We searched MEDLINE, EMBASE, the Cochrane Library, Web of Science, Open-SIGLE databases, ClinicalTrials.gov and the metaRegister of Controlled Trials on July 27, 2020 for relevant studies on the timing of antibiotic therapy in adult patients with sepsis or septic shock. The primary outcome measure was all-cause crude or adjusted mortality at reported time points. Results: We included 35 sepsis studies involving 154, 330 patients. Nineteen studies (54%) provided information on the appropriateness of antibiotic therapy in 20, 062 patients of whom 16, 652 patients (83%) received appropriate antibiotics. Twenty-four studies (68.6%) reported an association between time-to-antibiotics and mortality. Time thresholds associated with patient's outcome varied considerably between studies consisting of a wide range of time cutoffs (1 h, 125 min, 3 h or 6 h) in 14 studies, hourly delays (derived from the analyses of time intervals ranging from to 1 to 24 h) in 8 studies or time-to-antibiotic in 2 studies. Analyses of subsets of studies that focused on patients with septic shock (11 studies, 12, 756 patients) or with sepsis (6 studies, 24, 281 patients) yielded similar results. Conclusions: While two-thirds of sepsis studies reported an association between early administration of antibiotic therapy and patient outcome, the time-to-antibitiocs metrics varied significantly across studies and no robust time thresholds emerged.